The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11011-017-0005-5
|View full text |Cite|
|
Sign up to set email alerts
|

Novel magnetic resonance imaging findings in a patient with short chain acyl CoA dehydrogenase deficiency

Abstract: Reports on magnetic resonance imaging findings in patients with short chain acyl -Coenzyme A dehydrogenase (SCAD) deficiency, an autosomal recessive disorder caused by mutations in the acyl-Coenzyme A dehydrogenase (ACADS), are limited. Many asymptomatic carriers of ACAD variants have also been described necessitating careful evaluation of clinical and biochemical findings for an accurate diagnosis. Here we report a an infant with short chain acyl -Coenzyme A dehydrogenase (SCAD) deficiency diagnosed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…11 Chiplunkar et al have also recently reported an infant with hyperintensities in the white matter and basal ganglia that quickly progressed to cystic leukomalacia and atrophy. 12 Our patient's brain MRI findings indicate disturbed myelination with signs of multifocal leukoencephalopathy, which has not been reported so far at the course of the disease. Asymptomatic patients with SCADD have a very good outcome even when deleterious mutations are present.…”
Section: Discussionsupporting
confidence: 46%
“…11 Chiplunkar et al have also recently reported an infant with hyperintensities in the white matter and basal ganglia that quickly progressed to cystic leukomalacia and atrophy. 12 Our patient's brain MRI findings indicate disturbed myelination with signs of multifocal leukoencephalopathy, which has not been reported so far at the course of the disease. Asymptomatic patients with SCADD have a very good outcome even when deleterious mutations are present.…”
Section: Discussionsupporting
confidence: 46%
“…Previous reports of SCADD have described affected patients with multiple signs, including hypoglycemia, developmental delay, lactic acidosis, hypotonia, seizures, and cardiomyopathy, who exhibit variable responses to treatment and different outcomes (30)(31)(32). Of particular note, the most frequent autosomal recessive variant of the ACADS gene in our center was c.1031A>G (p. E344G) in exon 9.…”
Section: Discussionmentioning
confidence: 70%
“…Previous reports of SCADD have described affected patients with multiple signs, including hypoglycemia, developmental delay, lactic acidosis, hypotonia, seizures, and cardiomyopathy, who exhibit variable responses to treatment and different outcomes (30)(31)(32). Of particular note, the most frequent autosomal recessive variant of the ACADS gene in our center was c.1031A>G (p. E344G) in exon 9.…”
Section: Discussionmentioning
confidence: 70%